A tale of two heatwaves: variable daily growth and a broad diet enable neustonic larval cabezon to thrive during warm oceanic conditions - Megan N. Wilson; Megan N. Wilson; Richard D. Brodeur; Toby D. Auth; G. Curtis Roegner; Cheryl A. Morgan; Samantha M. Zeman; Su Sponaugle (Frontiers in Marine Science, 2025)
Effects of climate change on ocean ecosystem dynamics are widespread. Oceanographic conditions vital to biological communities have already shown changes, resulting in negative impacts on several of the world’s largest fisheries. The Northern California Current (NCC) is a highly productive system that supports many important fisheries. In addition to large-scale oceanographic forcing and seasonal up- and downwelling cycles, in the last decade, the NCC also experienced two distinct marine heatwaves (MHWs) that resulted in pervasive ecosystem alterations. The 2014–16 and 2019 MHWs had contrasting oceanic and atmospheric origins and different effects on ocean temperature, providing the opportunity to identify the mechanisms important to juvenile fish recruitment processes and how they may be differentially impacted by future warming scenarios. We utilized a five-year time series (2014, 2015, 2016, 2018, and 2019) of larval fish concentration, growth, and diet as a natural experiment to investigate the impact of MHWs as well as two neutral years on cabezon (Scorpaenicthys marmoratus). Findings include the first published measurement of larval cabezon daily growth rates. Mean growth rates were higher during MHWs, suggesting that elevated temperatures did not pose a major growth or survival challenge. Cabezon’s fast growth response to MHW conditions demonstrates that larval cabezon were able to sustain fast growth in warmer temperatures, and were not likely prey limited. Further, larval cabezon gut fullness did not differ significantly among years. Instead, differences in diet composition and prey quality varied with larval growth. Relative to slower-growing larvae, larval cabezon with high growth rates consumed larger prey items, including larval euphausiids and amphipods. Consistent with these patterns of larval growth, nearshore recruitment of juvenile cabezon was also high during MHW years. Our findings highlight the importance of phenological coupling, or matches in timing, between cabezon and euphausiid population dynamics in that larval cabezon exhibited fast growth when the timing of flexion was coupled with the euphausiid population transition to a larger, omnivorous larval stage. Results of this study suggest that larval cabezon’s variable growth and broad diet coupled with selection for large, nutrient dense prey may be a source of resilience for its population dynamics.